The fairy bargains of prospect hill eaudiobook - Miller, Rowenna (2023)
In this enchanting historical fantasy about sisterhood and self-discovery, a woman does everything she can to help her sister escape her husband— perfect for fans of C. L. Polk, Mary Robinette Kowal, and Marie Brennan. There is no magic on Prospect Hill—or anywhere else, for that matter. But just on the other side of the veil is the world of the Fae. Generations ago, the first farmers on Prospect Hill learned to bargain small trades to make their lives a little easier—a bit of glass to find something lost, a cup of milk for better layers in the chicken coop. Much of that old wisdom was lost as the riverboats gave way to the rail lines and the farmers took work at mills and factories. Alaine Fairborn's family, however, was always superstitious, and she still hums the rhymes to find a lost shoe and to ensure dry weather on her sister's wedding day. When Delphine confides her new husband is not the man she thought he was, Alaine will stop at nothing to help her sister escape him. Small bargains buy them time, but a major one is needed. Yet, the price for true freedom may be more than they're willing to pay. Praise for The Fairy Bargains of Prospect Hill : "A warm-hearted yet fierce fairy tale around the bonds of sisterhood."―H. G. Parry "Brimming with folk magic and delightfully sinister hidden worlds. Truly enchanting."―Leslye Penelope "A beautifully written tale of feminine power, sisterly devotion, and magic as old as the hills themselves."―Louisa Morgan For more from Rowenna Miller, check out: The Unraveled Kingdom Torn Fray Rule